Taxing Human Capital: A Good Idea - Christoph Braun (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2010)
This paper studies a Ramsey optimal taxation model with human capital in an infinite-horizon setting. Contrary to Jones, Manuelli, and Rossi (1997), the human capital production function does not include the current stock of human capital as a production factor. As a result, the return to human capital, namely labor income, does not vanish in equilibrium. In a stationary state, the household underinvests in human capital relative to the first best, i.e., education is distorted. Human capital is effectively taxed. The optimal tax scheme prescribes making the cost of education not fully tax-deductible. – – Dieser Beitrag untersucht ein Ramsey-Modell der optimalen Besteuerung mit Humankapital und einem unendlichen Zeithorizont. Im Gegensatz zu Jones, Manuelli und Rossi (1997) beinhaltet die Humankapitalproduktionsfunktion nicht den Bestand an Humankaptial als Produktionsfaktor. Daraus folgt, dass der Ertrag des Humankapitals, nämlich das Arbeitseinkommen, im Gleichgewicht nicht verschwindet. In einem stationären Gleichgewicht kommt es relativ zur erst-besten Lösung zu Unterinvestitionen in Humankapital, d.h., die Bildungsentscheidung ist verzerrt. Humankapital wird effektiv besteuert. Die optimale steuerliche Regelung schreibt vor, dass die Bildungskosten nicht voll steuerlich absetzbar sind.
Keywords: H21; I28; J24; 330; optimal taxation; human capital; Ramsey approach